Geophysical subsurface imaging for ecological applications - Jayawickreme, Dushmantha H (The New phytologist, 2014)
Ecologists, ecohydrologists, and biogeochemists need detailed insights into belowground properties and processes, including changes in water, salts, and other elements that can influence ecosystem productivity and functioning. Relying on traditional sampling and observation techniques for such insights can be costly, time consuming, and infeasible, especially if the spatial scales involved are large. Geophysical imaging provides an alternative or complement to traditional methods to gather subsurface variables across time and space. In this paper, we review aspects of geophysical imaging, particularly electrical and electromagnetic imaging, that may benefit ecologists seeking clearer understanding of the shallow subsurface. Using electrical resistivity imaging, for example, we have been able to successfully show the effect of land-use conversions to agriculture on salt mobilization and leaching across kilometer-long transects and to depths of tens of meters. Recent advances in ground-penetrating radar and other geophysical imaging methods currently provide opportunities for subsurface imaging with sufficient detail to locate small (≥5 cm diameter) animal burrows and plant roots, observe soil-water and vegetation spatial correlations in small watersheds, estuaries, and marshes, and quantify changes in groundwater storage at local to regional scales using geophysical data from ground- and space-based platforms. Ecologists should benefit from adopting these minimally invasive, scalable imaging technologies to explore the subsurface and advance our collective research